Exploring success in sub-acute hospital-to-home transitions for palliative patients: a descriptive qualitative study - MacLeod, Krystal K.; Shorting, Taylor; McCoy, Madeline; Bush, Shirley H.; Lalumière, Genevieve; Rice, Jill; Isenberg, Sarina R. (Université d'Ottawa | University of Ottawa, 2025)
Abstract Background Transitioning from a sub-acute hospital to home is highly desirable to some palliative and end-of-life individuals and their family caregivers, but the transition process itself is complex and can be logistically challenging. This formative assessment sought to better understand what constitutes a successful sub-acute hospital-to-home transition from the perspectives of health care providers connected to a sub-acute care facility in Ottawa, Canada, with reflections from a patient and a family caregiver. Methods Our descriptive qualitative study involved 13 virtual interviews and one virtual focus group between February and May 2023. Our sample included health care providers involved in the sub-acute hospital-to-home transition for palliative patients from a sub-acute facility, as well as one patient and one family caregiver who had experienced a palliative transition in this context. We used reflexive thematic analysis to code the data, and we inductively developed themes based on participants’ experiences. Results We collected data from 14 health care providers, one patient, and one family caregiver who were involved in, or had experienced, a sub-acute hospital-to-home transition. We found three themes delineating participants’ shared perceptions of the key foundations of a successful sub-acute hospital-to-home transition in the palliative context: meeting patient goals; sharing information to ensure informed decision-making; and having someone to coordinate the transition. Conclusions Our study highlighted that a successful sub-acute hospital-to-home transition should be person-centred and requires effective communication and coordination, both within and across, hospital and home environments. These insights will help inform intervention co-design to improve palliative care transitions in the next phase of this project.